2022
DOI: 10.1108/jsbed-07-2021-0279
|View full text |Cite
|
Sign up to set email alerts
|

Virtue or vice? Public policies and Nigerian entrepreneurial venture performance

Abstract: PurposeThe purpose of this paper is to explore how inter-agency engagement across levels of government and the agencies' policies impact the development of Micro, Small and Medium Scale Enterprises (MSMEs) in Nigeria, with focus on taxation, business registration and access to finance.Design/methodology/approachThe empirical study involved data sourced through questionnaire administered to 192 MSMEs owners, semi-structured interviews with key officials, and Focus Group Discussion (FGD) with leading members of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…[Insert Figure 3 here] policymakers in sub-Saharan African countries need to look for ways to promote the effectiveness of these gender-based policies (Edoho, 2016;Olorunshola and Odeyemi, 2023), which could include an evaluation of the existing gender-based policies such as access to credit, signing contracts, business registration, and bank account, to identify a unique configuration of gender-based policies suitable in supporting women's entrepreneurship in this social cultural contexts. Before proceeding to the theoretical contributions of this study, we discuss in detail four implications of our findings.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[Insert Figure 3 here] policymakers in sub-Saharan African countries need to look for ways to promote the effectiveness of these gender-based policies (Edoho, 2016;Olorunshola and Odeyemi, 2023), which could include an evaluation of the existing gender-based policies such as access to credit, signing contracts, business registration, and bank account, to identify a unique configuration of gender-based policies suitable in supporting women's entrepreneurship in this social cultural contexts. Before proceeding to the theoretical contributions of this study, we discuss in detail four implications of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a recent study of Sub-Saharan Africa, the World Bank (2022) found that women in Sub-Saharan Africa are still underrepresented in entrepreneurship and ownership of businesses due to cultural, legal, and institutional barriers that hinder women from accessing the resources and opportunities needed to start and grow businesses. Previous works have reported that a proactive gender-based policy is required for women's entrepreneurship to be successful (Azmat and Fujimoto, 2016;Ogundana, 2022;Olorunshola and Odeyemi, 2023;Ogundana et al, 2023). With a proactive gender-based policy on signing contact', 'business registration' and 'bank account', women's entrepreneurship is likely to be successful.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations